REDUPLIKASI DALAM NOVEL GARIS WAKTU KARYA FIERSA BESARI (KAJIAN MORFOLOGI) - Sinta Prihatiningrum Simatupang; Sumiharti Sumiharti; Uli Wahyuni (Universitas Batanghari, 2020)
The purpose of this research is to describe the reduplication in the aspect of form and meaning in the novel Garis Waktu by Fiersa Besari. This research is a qualitative descriptive. The data are in the form of expressions found in the novel Garis Waktu by Fiersa Besari. Based on the data analysis, thera are 190 expressions of reduplication are found. In the aspect of reduplication, 158 citations were found, with the following details; 1) the most dominant form of reduplication found was whole repetition that was 110 expressions; The dominant form of reduplication is the repetition of affixes that was 34 expressions; the least repetition form were 23 expressions, namely partial repetition; and the form of repetition of phoneme changes found in 3 expressions. As for the aspect of the meaning of reduplication, 32 expressions were found, with the following details: the most dominant meaning of reduplication is seven expressions that was